'Aargh! This Essay Makes Me Want to Poke Sticks in My Eyes!' Developing a Reader Engagement Framework to Help Emerging Writers Understand Why Readers Might (Not) Want to Read Texts - Haas, Sarah S (Journal of Academic Writing, 2018)
This paper outlines the development of the “Reader Engagement framework”, a tool for helping emerging writers understand what might keep readers reading – or stop readers from reading – a text. The Reader Engagement framework has been under development for the past five years, primarily in the context of undergraduate English proficiency classes at a large university in Flanders. Using the principles of constructivist grounded theory (Charmaz 2014), a preliminary framework was sketched using as data the margin comments of one reader who noted points of engagement or disengagement while reading student texts. Additional rounds of data collection included the engagement perceptions of student-readers, as well as those of teacher-readers from various disciplines. Thus far 1087 readers have been consulted, and the categories in the framework seem to be largely saturated. Though further refinement is necessary, the framework has been found successful as a teaching tool, and as an assessment and feedback tool. It also seems to have potential for offering writers a new way of conceptualising writing.